A sylvatic lifecycle of Echinococcus equinus in the Etosha National Park, Namibia. Issue 1 (April 2015) - Wassermann, Marion; Aschenborn, Ortwin; Aschenborn, Julia; Mackenstedt, Ute; Romig, Thomas
Graphical Abstract: Highlights: A wildlife cycle of Echinococcus equinus exists in the Etosha National Park. Lions, jackals and plain zebras are host of E. equinus . Haplotype identity and diversity was similar to samples from Europe. Abstract: Various species of Echinococcus have been described in the past from wild mammals of sub-Saharan Africa. However, it is only recently, that a few isolates have become available for molecular identification; therefore, the involvement of wildlife in the lifecycles of the various cryptic species within Echinococcus granulosus sensu lato is still only partially known. A preliminary survey was undertaken in Etosha National Park, Namibia, from August to October 2012. Faecal samples were obtained from 34 individual wild carnivores, and metacestodes were collected from carcasses of 18 culled herbivores. Single eggs and metacestode tissue were lysed and identified from sequences of the mitochondrial nad1 gene. In case of metacestodes, the cox1 gene was additionally sequenced and haplotype networks were constructed. Echinococcus equinus was found in lions (4 of 6), black-backed jackals (2 of 7) and Burchell's zebras (11 of 12). The frequency of this parasite in the absence of domestic dogs, horses and donkeys strongly indicates its transmission in a wildlife cycle. Further, a variety of sequences were obtained from eggs and cysticerci from lions, cheetahs, caracals, spotted hyenas and oryx, which most closely clustered with species of Taenia . Only 3 of them, 2 of lion and 1 of hyena origin, could be allocated to Hydatigera (=Taenia) taeniaeformis (lion), Taenia regis (lions and oryx) and Taenia cf. crocutae (spotted hyena and oryx).